Complete intersections : a guide to reconstructing intersections and interchanges for bicyclists and pedestrians. - Alta Planning + Design; Cambridge Systematics
Intersections and interchanges are major points of conflict for road users and are the frequent site of injuries and fatalities. In California, nearly 20 percent of pedestrian fatalities, and nearly a quarter of bicyclist fatalities occur at intersections. Intersections also have a significant impact on the mobility of pedestrians and bicyclists. The speed and ease with which they can move through an intersection is affected by the signal timing scheme, the number and configuration of lanes, width of the traveled way, presence of a median or refuge islands, traffic calming configurations, roadsides, landscaping features, traffic volumes, and other factors. Improving both safety and mobility at intersections for pedestrians and bicyclists presents a significant technical challenge for planners, engineers and other highway designers due to the complexity of the road environment and the number of tradeoffs to consider. This Guide is intended to help meet that challenge by presenting common issues faced by pedestrians and bicyclists at intersections and interchanges and best practices for addressing them through design and operational changes.